Implementing ‘CLEAR TB’ for Early Detection of Infectious Diseases in Visitors at the Pakusari Primary Health Care: Implementasi CLEAR TB untuk Deteksi Dini Penyakit Menular Pada Pengunjung di Puskesmas Pakusari Kabupaten Jember (AgroNurse Kesehatan : Jurnal Pengabdian Masyarakat, 2024)
Infectious diseases (IBD) are a major health problem in Indonesia, especially tuberculosis. Tuberculosis is one of the most common causes of death in the world and kills around 1.5 million people each year in 2020. In January-August 2024 at the Pakusari Health Center, data on TB cases found and treated were 76 patients, suspected TB patients who received standard diagnostic services were 732 patients, the success rate of treatment was 42 patients, TB patients who underwent contact investigations were 68 patients, health services for people with suspected TB were 732 patients, and TB in children were 7 patients. From these data, it can be concluded that the transmission of this disease is still high even though a Pulmonary TB control program has been carried out. In order to detect tuberculosis infectious diseases early in patients at the Pakusari Health Center, we created the CLEAR TB innovation program. This community service activity is in the form of implementing CLEAR TB for visitors to the Pakusari Health Center which includes integrated services based on an online screening approach through an application. CLEAR TB stands for Check Active Evaluation Steps for Tuberculosis Risk. The purpose of this community service is to develop a program for prevention and control of infectious diseases of TB to make it more accessible, especially in the Pakusari Health Center area and to increase service satisfaction for the community. In addition, it makes it easier for health workers to screen suspected tuberculosis patients.